Pod znakom Pi . Pod znakom Pi . Under the Sign of Pi . Под знаком Пи - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Retrospective of the popular science program "Obvious and Unbelievable" and "Under the sign of Pi," from the 1970-80s. Featured in the program: Plisetskaia, Maiia Mikhailovna (Ballet Dancer); Ponarovskaia, Irina (Singer) Contributors: Kapitsa, Sergei (Anchor) Ретроспектива выпусков научно-популярной передачи "Очевидное и невероятное" и "Под знаком Пи" 1970-80х годов. В программе участвуют: Плисецкая, Майя Михайловна (Артистка балета); Понаровская, Ирина (Певица) Создатели: Капица, Сергей (Ведущий/Ведущая)